EXPLORATION FIGURATIVE LANGUAGE IN WESTLIFEâ€™S SONGS - Pandanwangi, Gisha; Anggraeni, Anita (PROJECT (Professional Journal of English Education), 2021)
Figurative language is the ways to show special language that the soul and the writer personality. The language in song lyrics tends to be like the language of poetry. The author is interested in analyzing some of the figurative language contained in a song. Figurative language is often used by a writer, so the creation that has been made becomes more interesting. In this research, the researchers will try to analyze a Westlife songs with the title of â€œFragile Heartâ€ and â€œI doâ€. There are many figurative language that we can find in a songs or novels. They used figurative language to change the true meaning. The purpose of learning about figurative language is to understand the message of a sentence conveyed imaginatively in spoken or written form by the author.Â Keywords:Â  Figurative language, Meaning, Lyrics